Sharing the adventure with the student : exploring the intersections of NASA space science and education : a workshop summary - Day, Dwayne A. (National Academies Press, 2015)
"On December 2-3, 2014, the Space Studies Board and the Board on Science Education of the National Research Council held a workshop on the NASA Science Mission Directorate (SMD) education program - "Sharing the Adventure with the Student." The workshop brought together representatives of the space science and science education communities to discuss maximizing the effectiveness of the transfer of knowledge from the scientists supported by NASA's SMD to K-12 students directly and to teachers and informal educators. The workshop focused not only on the effectiveness of recent models for transferring science content and scientific practices to students, but also served as a venue for dialogue between education specialists, education staff from NASA and other agencies, space scientists and engineers, and science content generators. Workshop participants reviewed case studies of scientists or engineers who were able to successfully translate their research results and research experiences into formal and informal student science learning. Education specialists shared how science can be translated to education materials and directly to students, and teachers shared their experiences of space science in their classrooms. Sharing the Adventure with the Student is the summary of the presentation and discussions of the workshop."--Publisher's description